Reformed theology and natural science – Conflict or concurrence? - Izak J. van der Walt (In die Skriflig, 2020)
Atheistic natural scientists propagate a normative materialistic view of the universe, where God as creator is superfluous. Much effort is being expended to bring into disrepute any notion of extraneous control over the laws of nature. The idea of the universe and everything in it as an ongoing ‘cosmic accident’ is presented as the only truth. This is in stark contrast to recent scientific discoveries in disciplines such as biochemistry and palaeontology. In this article, the most recent developments in the fields of intelligent design and the anthropic principle will be interrogated to demonstrate that the reformed faith in God as Creator is credible and that the notion of creation as God’s general revelation to humankind is increasingly being accepted by the natural scientific community.